A thematic analysis of the experiences of prepubertal transgender and gender-diverse children in Sweden - Tyni, Kristiina; Wurm, Matilda; Sofia Bratt, Anna (International Journal of LGBTQ+ Youth Studies, 2025)
Knowledge of prepubertal transgender and gender diverse (TGD) children is limited. This study fills a gap in the research literature by exploring the lived experiences of prepubertal TGD children related to gender identity, centering their voices. Interviews with 10 TGD Swedish children 4-12 years old were analyzed through Thematic Analysis. The analysis resulted in two main themes: (1) "The journey of gender exploration," with subthemes Discovering me and The joys, and challenges of being me; (2) "Meeting the outside world," with subthemes Can I belong? and Staying me: my tips, tricks and help from others. The children's evolving gender identity was traced, emphasizing emotional aspects and pivotal milestones like affirmed names. Even though the children had supportive environments, challenges of misgendering and the need for continual self-assertion were exposed. Despite struggles for recognition, the study highlights TGD children's resilient coping and well-being. Still, cisgender norms were observed to challenge their prevalent pride and positive self-images, emphasizing the need for enhanced knowledge of gender diversity for a broader societal change. This study expands the literature on TGD children's gender identity development, informs professionals and a broad audience and provides an enhanced understanding of TGD prepubertal children through their own words.